Primitive structural method for high capacity text steganography - Roslan, Nuur Alifah; Mahmod, Ramlan; Udzir, Nur Izura; Ahmad Zulkarnain, Zuriati (Asian Research Publication Network, 2014)
High capacity for hiding secret information is typically the main concern in text steganography, as well as robustness and perceptual invisibility in a perfect steganography algorithm. The major issue in text steganography is the difficulty of using a large amount of redundant information to hide secret bits (1 and 0) in perceptible appearance. We propose a Primitive Structural algorithm for Arabic text steganography to encounter this issue. This algorithm hides the secret bits in the primitive structure (i.e. sharp edges, dots, typographical proportion) for the Arabic character. Therefore, this new algorithm presents a high data-embedding capacity since each character has more than one potential place to hide the secret information. The main processes involved are the preparation of the secret message as a binary process, identifying the Primitive Structural for each character in the cover-text process, and finally the bit hiding process. The experiments have shown that the data-embedding capacity percentage is increased up to 4% for our first experiment and for the second experiment the results show the increase in capacity up to 21% compared to the our previous method, thus resolving the capacity issue.